Interleukin-17 and acute coronary syndrome - Su, Sheng-an (Zhejiang University Press, 2013)

(untitled)
Inflammation plays an important role in atherosclerosis, which is also crucial for acute coronary syndrome (ACS). Recent studies have revealed that interleukin (IL)-17, which was regarded as a pro-inflammatory cytokine, has a dual function in the progress of ACS. In this review, we sum up both experimental and clinical studies on the relevance of IL-17 to atherosclerosis and its complications, and summarize the research progress on the effect of IL-17 on the atherosclerotic plaque stability and ACS onset. Although the studies are controversial and the mechanism remains unclear, we highlight the knowledge of the role of IL-17 in ACS and elucidate its potential mechanism.